Interannual variability and evolution during the montanera period of Holm oak (Quercus rotundifolia Lam.) acorns - Tejerina, D.; García-Torres, S.; Cabeza de Vaca, M.; Cava, R.; Vázquez, F. M. (Spanish Journal of Agricultural Research, 2010)
Eighty-eight samples of Quercus rotundifolia acorns were analyzed during three consecutive years (2005/06, 2006/07 and 2007/08) to determine variations in their morphology, sanitary condition, and nutritional composition throughout the same period of montanera (free-range swine-raising system of SW Iberia) and between different years of study. Results showed that morphological characteristics remained constant throughout montanera season. Fungal damage increased, and Curculio sp. and Cydia sp. pests decreased over the course of the montanera season. Dry matter content decreased in both kernel and pericarp (P < 0.001), while the crude fiber and protein contents were not modified. The ash, nitrogen-free extract, and fat contents, however, were also affected by sampling date within a montanera season. With respect to the interannual variability, variations (P < 0.05) were observed in all the variables studied. It is therefore confirmed that there is variability in the sanitary condition and nutritional composition of acorns within the same montanera season and between different years of study. These could explain the differences in the chemical characteristics of Iberian pig tissues from animals raised in different montanera seasons, and even during the same montanera season.
Keywords: acorn sanitary condition; Dehesa; feeding; Iberian pigs; proximate composition

How do vigilance and feeding by common cranes Grus grus depend on age, habitat, and flock size? - Avilés, Jesus M.; Bednekoff, Peter a (Journal of Avian Biology, 2007)
Animals often spend less time vigilant and more time feeding when foraging in larger groups. This group-size effect does not, however, consider if larger groups differ systematically from smaller ones: Large groups could form in different habitats than small groups or be composed of a different mix of ages or classes than small groups. We examined how habitat differences and flock size and composition explain feeding and vigilance rates in common cranes Grus grus, wintering in holm oak Quercus ilex dehesas of Spain. Flock size and composition were related to habitat type in cranes: flocks formed in areas sown with cereal crops were larger than flocks formed in set aside areas. Vigilance rate depended on habitat but decreased with increasing flock size in a similar way across all habitats. Juveniles were less vigilant than adults and showed little change in vigilance with flock size. Vigilance increased and feeding time decreased over months from November through February. Our results show that vigilance is affected by habitat but that the group size effect on vigilance is not the product of differences between habitats in group size or composition.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Cranes; Dehesa; feeding; flock size; holm oak canopy (voyant); vigilance

Effect of feeding system on the growth and carcass characteristics of Iberian pigs, and the use of ultrasound to estimate yields of joints. - Daza, a; Mateos, A.; López Carrasco, C.; Rey, A.; Ovejero, I.; López-Bote, C. J. (Meat science, 2006)
Forty three-castrated male Iberian pigs of the Torbiscal line with an average initial weight of 102.27kg were used. A group of 22 pigs was fed according to the traditional way in free-range conditions with acorn and grass from November to January. Another group of 21 animals was fed 3.72kg/day of a conventional feed that contained 12.53MJME/kg, 16.21% crude protein, 4.94% fat and 6.64% of crude fiber, during the same period. Measurements of backfat thickness and Longissimus dorsi muscle area at the last rib were taken by means of a real-time ultrasound device (Kretz Technick Inc., 600 V-V2.32, Sonovet, Austria) in all pigs before slaughter. After slaughter, carcass, ham and foreleg weights and backfat and muscle area measurement from the last rib chop were recorded. The average daily gain, carcass yield, fat thickness, loin area, ham weight and proportion of hams were significantly higher (P<0.05) in the pigs fed in confinement than in those fed extensively (653.36g, 77.97%, 56.46mm, 3031mm(2), 22.26kg and 14.32% vs 501.48g, 76.94%, 51.74mm, 2673mm(2), 21.52kg and 13.79%, respectively). This paper shows the prediction equations for hams, forelegs and total hams and forelegs weights and proportions with respect to slaughter weight and live ultrasound measurements in pigs fed either extensively or in confinement. The ultrasound measurements better predicted the carcass cuts absolute amounts (R(2)=0.591-0.875) than the carcass cuts proportions (R(2)=0.23-0.40). The use of real-time ultrasound should be used with caution to predict the absolute quantities of hams and forelegs from Iberian pigs since the ultrasound measurements are only moderately accurate.
The following values have no corresponding Zotero field: accession-num: 22061368
Keywords: carcass; feeding; Growth; iberian pig; ultrasounds

PRODUCCION DE BELLOTA EN QUERCUS ROTUNDIFQLIA LAM.: VARIABILIDAD ANUAL E IMPORTANCIA ECONOMICA - Esparrago, F.; Vázquez, F. M.; Burzaco, A.; Perez, M. C. (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The acorn production on Q. rotundifolia Lam. has been analyzed from 1989 through 1992 in Extremadura. The efects of different areas, each tree, and the interaction between areas/years are significatives. Genetic, pruning, environment and phytosanitary factors are the possible causes of these differences. Finally, the econornic efects of acorn production on iberian pig feeding (Montanera) has been studied. This is the rnain factor for high quality products.
The following values have no corresponding Zotero field: periodical: Congreso Forestal Español, Lourizán - Pontevedra. 1993
Keywords: acorn; Econorny; evergreen oak; feeding; iberian pig; production; Quercus